First isolation of Toxoplasma gondii from rodents and stray cats in northeast of Iran - BAHADORI, EHSAN SHARIAT; SADRAEI, JAVID; DALIMI, ABDOLHOSEIN; NAMROODI, SOMAYYEH; PIRESTANI, MAJID (The Indian Journal of Animal Sciences, 2019)
Toxoplasma gondii is a common coccidian parasite with stray cat family as definitive host, and a wide range of warm blooded animals and human as intermediate hosts. The objective of this study was to isolate T. gondii from rodents and stray cats in northeast of Iran. Genomic DNA was extracted from 30–50 mg of the rodents and stray cats’ tissue using phenol-chloroform extraction method. Using PCR-RFLP, the genes (SAG1, SAG3, GRA6, 18SrRNA) and sequencing method, the isolation of T. gondii from these hosts was determined. ELISA method was also used on serum samples to evaluate the IgG antibodies against T. gondii among the hosts. Out of 286 rodents and 210 stray cats tested, the DNA of T. gondii was detected in 68 and 38 samples, respectively. Nucleotide sequencing and phylogenetic analysis confirmed the RFLP results. It was also observed that dominant genotype of T. gondii in infected rodents and stray cats belonged to genotype 3. The results of this study indicated that rodent and stray cat hosts can play an important role in maintaining the Toxoplasma transmission cycle in the Golestan province.